Modified ulnar lengthening for correction of the Masada type 2 forearm deformity in hereditary multiple exostosis - Shu Cao; Jian-Fa Zeng; Sheng Xiao; Zhong-Gen Dong; Zi-Li Xu; Hong Liu; Xin Li; Ke Fang; Jie Wen; Ming Zeng; Zhong-Wen Tang; Bo Li; et al. (Scientific Reports, 2023)
Abstract Few articles have reported on the treatment of Masada type 2 forearm deformities in hereditary multiple exostosis, possibly because of the high redislocation rate and other complications. This study precisely declares the use of modified ulnar lengthening by an Ilizarov external fixation with tumour excision for the treatment of Masada type 2 forearm deformities. 20 children with Masada type 2 forearm deformities were admitted for surgical treatment at our hospital from February 2014 to February 2021. There were 13 girls and 7 boys, ranging in age from 3.5 to 15 years (mean: 9 years) at the time of operation. We removed the prominent osteochondromas of the distal ulna and the proximal radius, positioned a classic Ilizarov external fixator on the forearm and then performed ulnar transverse one-third proximal diaphyseal subperiosteal osteotomy. We adopted modified ulnar lengthening postoperatively. The effects of surgical correction of deformity and functional improvement of the limb were assessed via regular follow-up and X-ray. The patients were followed up for 36 months, and the ulna was lengthened 26.99 mm on average; all radial heads remained relocated. The radiographic evaluations, including relative ulnar shortening, radial articular angle, and carpal slip, were improved. The functions of the elbow and forearm were all improved after surgery. Modified ulnar lengthening by an Ilizarov external fixation with tumour excision for the treatment of Masada type 2 forearm deformities in hereditary multiple exostoses has been proven to be an effective and reliable technique in the early stage.